2005
DOI: 10.1158/0008-5472.can-04-3900
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity and Oxygen Dependence of Glucose Consumption in R3230Ac and Fibrosarcomas of the Fischer 344 Rat

Abstract: To examine the oxygen-dependence of glucose consumption in solid tumors, we monitored gradients of glucose, lactate, and hypoxia in R3230Ac and FSA tumors growing in Fischer 344 rats. Bioluminescence imaging, detection of Hoechst 33342, and immunostaining of the hypoxia marker EF5 [2-8-N-(2,2,3,3,3-pentafluoropropyl)acetamide] were done in serial tumor slices. Glucose and lactate levels were also determined in liver and blood. Cells were further tested for glucose consumption and lactate production in vitro. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 33 publications
3
104
0
Order By: Relevance
“…Under hypoxic conditions, cells favor glycolysis over oxidative phosphorylation for ATP production. Neoplastic cells also favor glycolysis over oxidative phosphorylation (1,28), so the measured decreases in NADH lifetimes and the contribution of protein-bound NADH with precancer are consistent with the increased levels of glycolysis that are expected in neoplastic cells. Changes in the distribution of NADH enzyme binding sites associated with preferred metabolic pathways in neoplastic tissues (6) may be responsible for the change in protein-bound NADH lifetime with precancer.…”
Section: Discussionmentioning
confidence: 57%
“…Under hypoxic conditions, cells favor glycolysis over oxidative phosphorylation for ATP production. Neoplastic cells also favor glycolysis over oxidative phosphorylation (1,28), so the measured decreases in NADH lifetimes and the contribution of protein-bound NADH with precancer are consistent with the increased levels of glycolysis that are expected in neoplastic cells. Changes in the distribution of NADH enzyme binding sites associated with preferred metabolic pathways in neoplastic tissues (6) may be responsible for the change in protein-bound NADH lifetime with precancer.…”
Section: Discussionmentioning
confidence: 57%
“…Doing an analysis very similar to ours, Pugachev et al 13 demonstrated a highly significant positive spatial correlation (r 5 0.50-0.66) between the distribution of 18 F-FDG and pimonidazole in the rat prostate cell line R-3327-AT, but this cell type may, as SiHa, be an outlier with a particularly high dependency on mitochondria-derived ATP (i.e., a large Pasteur effect is expected). In contrast, Schroeder et al 25 suggested than even in cells retaining a significant Pasteur effect in vitro, areas of viable hypoxic cells and low glucose uptake may coexist in the tumor, because hypoxic cells may be partly glucose starved. This could possibly explain areas of hypoxia, but with relatively low 18 F-FDG uptake in UT-SCC-33 (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…This may reflect a lowered capacity to switch from aerobic to anaerobic metabolism, resulting in lower threshold for cell death [26]. We have shown previously that both oxygen and glucose gradients contribute to nutrient depletion and necrosis [27]. Additional studies to examine nutrient gradients in these tumor models might yield mechanistic information underlying the contribution of nutrient depletion to necrosis.…”
Section: Discussionmentioning
confidence: 98%